Through the Looking Glass - Tester, Keith (Studia Socjologiczno-Polityczne. Seria Nowa, 2017)
This page or two seeks to do nothing more than draw inspiration from Bauman’s work in order to raise some questions. I am not going to answer the questions because they are too important for me to pretend to be able to answer them. In any case this is not the time for answers. I have very deliberately kept this document very short in order to make the questions sharper. They need to be sharp because they need to be able to cut us out of the warm and soft belly of the whale in which academics write without however smelling the stench from the poisoned corpse.